INDEPENDENT CURRICULUM ASSESSMENT: IMPLEMENTATION AND CRITERIA FOR ACHIEVING LEARNING OBJECTIVES (KKTP) AT SMA NEGERI 3 SUNGAI KAKAP - Nur Meily Adlika (Jurnal Scientia, 2023)
The purpose of this research is to determine the implementation and determination of criteria for achieving learning objectives at SMA Negeri 3 Sungai Kakap. Changes to the independent curriculum certainly affect the assessment system for students. Both assessments are to provide information on improving the learning process, as well as to determine students' achievement of learning objectives. Each educational unit has a system for implementing and determining or creating different criteria for achieving learning objectives. Although they vary, the guidelines used are as provided by the Ministry of Education, Culture, Research, Technology and Higher Education. This research uses a descriptive qualitative method. Data collection uses observation techniques, interviews and documentation studies. Analysis of research results was carried out according to Milles and Huberman's analysis. The results of this research on the implementation of assessments at SMA Negeri 3 Sungai Kakap are prioritizing the development of students' overall potential, rubric-based assessments that are comprehensive and inclusive. Meanwhile, in the Learning Goal Achievement Criteria replacing the minimum completeness criteria or KKM, teachers are advised not only to give absolute scores but to accompany them with descriptions regarding student abilities and the application of Learning Goal Achievement Criteria to measure the achievement of learning goals based on each student's abilities.